PENGUATAN SELF-CARE LANSIA DALAM MENGELOLA PENYAKIT KRONIS BERBASIS KELUARGA - Saumi Fijriyah; Endang Tri Sulistyowati; Rahma Trisnaningsih; Istiqomah Istiqomah; Siti Mahmudah (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2026)
The increasing elderly population is accompanied by a rising prevalence of chronic diseases requiring long-term and continuous management. Self-care is a key component in chronic disease management among older adults; however, it is often limited by insufficient knowledge and inadequate environmental support. Family plays a strategic role as the closest support system in strengthening elderly self-care capacity. This community service activity aimed to enhance elderly self-care in managing chronic diseases through a family-based approach. An educative–participatory method with a pre-experimental one group pre-test and post-test design was applied. The intervention consisted of health education, interactive discussions, and family assistance. Evaluation focused on changes in elderly knowledge, self-care practices, and family roles before and after the intervention. The results demonstrated improvements in elderly knowledge, self-care behaviors, and family involvement in chronic disease management. A family-based approach is effective in promoting elderly independence and supporting sustainable chronic disease management.